Analisis Harga Pokok Produksi Dengan Menggunakan Metode Variabel Costing Untuk Menentukan Harga Jual Pada Suhar Meubel Bengkulu - Yanti, Sri Darma (Journal of Management, Economic, and Accounting, 2022)
The purpose of this study was to determine how the calculation of the cost of production using the Variable Costing method in determining the selling price of the Suhar Furniture business in Bengkulu. The research was conducted using data for 6 months of production and using interview and documentation data collection methods and using variable costing method analysis methods.The results of the research and discussion of the calculation of the cost of production using the variable costing method in the Suhar furniture business in Bengkulu. In calculating the production costs of this company using the variable costing method, the overall calculation results obtained the selling price per unit of the door frame with the variable costing method of Rp. 473,000 per unit for the month July, August amounted to IDR 508,500, for September it was IDR 397,500, for October it was IDR 484,166, for November it was IDR 520,000, for December it was IDR 501,000, while the overall calculation results obtained the selling price per unit of window frames using the variable costing is Rp. 276,875 per unit for July, for August it is Rp. 274,000, for September it is Rp. 283,928, for October it is Rp. 282,236, for November it is Rp. 292,500, for December it is Rp. 268,269.